2020
DOI: 10.1111/psyp.13553
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal‐on‐foveal repetition effects in sentence reading: A co‐registered eye‐tracking and electroencephalogram study

Abstract: When reading, can the next word in the sentence (word n + 1) influence how you read the word you are currently looking at (word n )? Serial models of sentence reading state that this generally should not be the case, whereas parallel models predict that this should be the case. Here we focus on perhaps the simplest and the strongest Parafoveal‐on‐Foveal (PoF) manipulation: word n + 1 is either the same as word n or a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…However, the approach is limited, as changing the target word inevitably disrupts the integration of information across fixations and interferes with natural reading. This interference has been shown in many gaze-contingent studies in which reading performance is reduced when words are manipulated in the parafovea 17,[49][50][51] . Fixation or event-related potentials based on EEG is another method used in reading studies [52][53][54][55] , and have shown different brain activity patterns for different word presentation rates, addressing the importance of using natural reading paradigms 56 .…”
Section: Discussionmentioning
confidence: 75%
“…However, the approach is limited, as changing the target word inevitably disrupts the integration of information across fixations and interferes with natural reading. This interference has been shown in many gaze-contingent studies in which reading performance is reduced when words are manipulated in the parafovea 17,[49][50][51] . Fixation or event-related potentials based on EEG is another method used in reading studies [52][53][54][55] , and have shown different brain activity patterns for different word presentation rates, addressing the importance of using natural reading paradigms 56 .…”
Section: Discussionmentioning
confidence: 75%
“…That is, when reading the sentence 'The boy picked the rose from the garden', reading times of the target word 'rose' should not be influenced by the replacement of the parafoveal word 'from' with a pseudohomophone 'roze' prior to the eyes moving to that location. This predicted null effect could be contrasted with well-established orthographic parafoveal-on-foveal effects obtained during sentence reading (Angele, Tran, & Rayner, 2013;Dare & Shillcock, 2013;Mirault et al, 2020;Snell, Vitu, & Grainger, 2017). Such additional experimentation would further help connect the results obtained with the flankers task and those obtained in more natural reading situations (for a recent debate, see Snell & Grainger, 2019;and accompanying commentaries, Schotter & Payne, 2019;White, Boynton, & Yeatman, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…In sentence reading tasks, typically, a one-line sentence (Degno et al, 2019a(Degno et al, , 2019bDimigen et al, 2011;Kretzschmar et al, 2009Kretzschmar et al, , 2015Loberg et al, 2018Loberg et al, , 2019Metzner et al, 2015Metzner et al, , 2017Mirault et al, 2020;Weiss et al, 2016), or longer passages of text (Henderson et al, 2013), is presented on the screen, and participants are required to read each sentence to then answer comprehension questions. By presenting grammatical text (minimally a single sentence, and potentially longer texts), readers can form a meaningful interpretation of the text beyond isolated word meaning, and all aspects of EM behaviour during reading (e.g., skipping), as well as the participant's task (i.e., reading for comprehension without a secondary task) are natural.…”
Section: Sentence Readingmentioning
confidence: 99%
“…Thus, both pre-target and target words are considered regions of interest in the present pipeline. However, researchers might select only pre-target or only target words as regions of interest, if for example only parafoveal-on-foveal effects are examined (e.g., pre-target word only, Mirault et al, 2020), or only foveal processing is to be studied (e.g., target words only, Hutzler et al, 2007). In addition, which observations need to be retained or discarded will also vary depending on the research question at hand.…”
Section: Preprocessing Of Data Preprocessing Of Datamentioning
confidence: 99%
See 1 more Smart Citation